Investigations on structural, optical and electrical property of ZnO-CuO core–shell nano-composite. (May 2019) - Kanani, M.V.; Dhruv, Davit; Rathod, H.K.; Rathod, K.N.; Rajyaguru, Bhargav; Joshi, A.D.; Solanki, P.S.; Shah, N.A.; Pandya, D.D.
Abstract: ZnO-CuO core–shell nano-composite was synthesized by two-stage assisted wet-chemical sol-gel method. The nano-composite investigated by X-ray diffraction, field effective scanning electron microscope, UV–visible spectroscopy and Electrical property at different frequency range 100 Hz to 2 MHz and at different temperature. The X-ray diffraction pattern shows poly-crystalline growth of sample, UV–visible spectrum shows higher absorption in ZnO-CuO nano-composite as compare ZnO, which can be understood in vicinity of morphology and heterojunction. The electrical conductivity of nano-composite has been increased with frequency and temperature due to defect available in the sample and thermal excitation of the charges in the sample respectively. Graphical abstract: Unlabelled Image